Influência de carnes PSE (pale, soft, exudative) na absorção e perda de água por gotejamento em caraças de frango - Queiroz, Christiane Aparecida Urzedo de (2015)
Chicken meat is a product with high demand, leading to a concern with the quality of this product, and stricter oversight by federal agencies. One of these concerns is excess water retained of exogenous nature in the carcasses during slaughter. Thus, the application of analytical methods for controlling the water content as Dripping test, in whole carcasses, has become extremely important for the inhibition of fraud of slaughterhouses and consequently on consumer protection. In ante mortem step, failures in handlings activities cause stress in birds and trigger reactions in the post mortem process, interfering with technological and sensory quality of the meat. The formation for PSE occurs when the muscle reaches final pH of 5.8 with high body temperature, denaturing the proteins, characterized by poor water retention, consequently has a tendency for greater loss than considered normal. The main objective of this study was to determine whether PSE carcasses compared with Normal are significant differences in the results of absorption and drip tests that can generate tax assessment to refrigerators. The samples were collected in an industrial plant, birds with 45-52 days of age, lineages Hubbard, Cobb, Ross and AP 91 and the chicken breast samples, Pectoralis major, classified as PSE, pH ≤ 5.8 and Standard, pH>5.8 and water absorption and dripping test measures followed the methodology described in Ordinance No. 210. The results showed no significant difference in the absorption Standard carcasses and PSE probably because at the time of absorption measuring, approximately 100 minutes after the bleeding, the proteins were not completely denatured, remaining with the water molecules linked. After the freezing step the glycolysis was completed with the full development of denaturation of proteins and thus, the PSE carcasses presented with values 0.81% higher of water loss measured by the drip test. The water absorption rate in the Pre-Cooling with water immersion follows the upper limit of 8% as required by the legislation, since all parameters are tightly controlled and absorptions do not differ significantly in different weights of carcasses. Other results showed that the drip test time required for the carcass to reach a temperature of 4°C internally, was 10,5 minutes less than that obtained following the established by the legislation. From these results, it is recommended that the monitoring of carcass process, the muscle to meat transformation, be properly monitored and it is suggested insert anomalous meat in the documents used today by MAPA, well as a review of temperature x time values to perform the Dripping test.